The Russia-Ukraine war after a year: Impacts on fertilizer production, prices, and trade flows - Hebebrand, Charlotte; Glauber, Joseph W. (International Food Policy Research Institute, 2023)
Russia’s 2022 invasion of Ukraine triggered global disruptions in markets for key food crops and fertilizers, threatening food security worldwide. With the war now entering its second year, high international food prices have moderated, though domestic price levels remain high in many low- and middle-income countries. Here, we turn to global fertilizer markets, examining how they weathered the past year, and the likely impacts going forward for agricultural production and food security.